Effect of sex hormones, garlic and fennel extracts in layers’ breeders diet on inherited offspring sex - Zeinab Bardel; Ali Asghar Saki; Asghar Mirzaie-Asl; Pouya Zamani (PLoS ONE, 2026)
This study aimed to examine the effect of dietary supplementation with sex hormones, garlic, and fennel extracts in layer breeders on the molecular sex ratio of their progeny. One hundred layer breeders, aged sixty-five weeks, were assigned to five treatments with five replicates of four hens each in a completely randomized design (CRD) for five weeks. The experimental treatments consisted of: (1) a control diet (corn and soybean meal-based), (2) control diet + testosterone (1 mg/kg), (3) control diet + progesterone (1 mg/kg), (4) control diet + fennel extract (400 mg/kg), and (5) control diet + garlic extract (400 mg/kg). In the third and fifth weeks of the experiment, blood samples were collected from the wing vein of layer breeders to measure sex hormone levels. At the end of the fifth week, eggs were gathered over two consecutive days and incubated at 37.5°C. The results suggest that fennel extract increased serum testosterone levels compared to the control throughout the study period ( P = 0.057). Garlic and fennel extracts and progesterone increased the female sex ratio, while testosterone treatment increased the male sex ratio compared to the control ( P = 0.056), although these differences were not statistically significant ( P > 0.05). The experimental treatments significantly influenced the percentage of embryos produced ( P < 0.05). No significant effect was observed on blood glucose levels ( P = 0.076), though numerical differences were noted. Treatment 2 (testosterone) resulted in the lowest female sex ratio and blood glucose levels, whereas treatments 3 (progesterone), 4 (fennel extract), and 5 (garlic extract) yielded the highest female sex ratios and blood glucose levels. These findings suggest that the treatments’ effects may be linked to their impact on blood glucose levels. The results indicate that dietary interventions affect the offspring sex ratio.